Impact of scientific production of Italian scientists in exercises and sport sciences by measuring the author-weighted h-index - Raiola, Gaetano; Esposito, Giovanni; Ceruso, Rosario; D'Elia, Francesca; D'Isanto, Tiziana (Frontiers in Research Metrics and Analytics, 2024)
This study aimed to measure the consistency of the impact of scientific production, weighted by authorship, of Italian scientists in two academic disciplines (AD) of Exercise and Sports Sciences (ESS) from 2017 to 2022, with a specific focus on the subfield “Sport Sciences”, using topic-specific keywords. Through the Scopus database, the scientific products of Italian ESS scientists associated with each keyword were identified. Subsequently, total and relative metric parameters from 2017 to 2022 were collected, including the total and relative number of citations. To evaluate the impact of the publications, the total and relative h-index were calculated, and weighted by considering different categories of authorship. Specific weights were attributed to each category: single author, first author, last author and co-author, following the classifications already in use on Scopus for each author. The trends of total and relative metrics, including citations and h-index, from 2017 to 2022 were analyzed using Spearman's correlation. Non-parametric linear regression analysis was used for the predictive analysis of these trends. Among the 83 identified ESS scientists, a detailed analysis revealed that 31.3% were full professors, 42.1% associate professors, and 26.6% researchers. Less than half of these scientists were directly affiliated with ESS. Despite minority representation, significant positive correlations emerge between total and relative citations from 2017 to 2022 (r = 0.687) and between the weighted total h-index and the weighted relative h-index (r = 0.965). Significant trends emerge in the metric parameters of the same scientists when analyzed separately by AD. The regression results indicate that variations in total citations and the weighted total and relative h-index can predict or explain the observed changes in 2017–2022 (p < 0.05). This result suggests that the production and impact of research in the field of ESS follow the same general trend as production and impact in the specific subfield.